Development of iSpring Suite-Based Learning Media Using Dual Coding Theory for Arabic Vocabulary - Nafilah Afifah Zain; Muhammad Ardy Zaini; Mokhammad Miftakhul Huda; Taha Ramadan Ibrahim Zaghloul (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2026)
Backgrounds: Mastery of Arabic vocabulary is essential for language proficiency; however, instruction in Islamic senior high schools remains dominated by memorisation and drill methods, resulting in low retention and limited integration of cognitively grounded digital media. Objectives: This study aims to analyse students’ needs in Arabic vocabulary learning, examine the feasibility of iSpring-based learning media grounded in Dual Coding Theory, and test its effectiveness in improving vocabulary mastery. Methods: The study employed a Research and Development (R&D) approach using the ADDIE model, combined with a one-group pre-test–post-test design. Data were collected through observations, interviews, questionnaires, and vocabulary tests, and analysed using a mixed-methods approach. Results:The results indicate that students require interactive digital media integrating visual and audio elements. The developed iSpring-based media was categorised as highly feasible based on expert validation. The effectiveness test involving 26 students (n = 26) revealed a statistically significant improvement in vocabulary mastery, as reflected by the increase in mean scores from pre-test (M = 68.85) to post-test (M = 77.31), t(25) = 7.04, p < 0.001, with a large effect size (Cohen’s d = 1.38). Conclusions: The findings demonstrate that the media is effective in enhancing students’ vocabulary mastery and engagemen